Immigration and social systems : collected essays of Michael Bomm es - Bommes, Michael; Boswell, Christina; D'Amato, Gianni (Amsterdam : Amsterdam University Press, 2012)
"This posthumous collection brings together a selection of [Michael Bommes's] most important work on immigration and the welfare state, imm igrant integration, discrimination, irregular migrations, migrant netwo rks and migration policy research."-- page 4 of cover.
Includes bibliographical references.
Keywords: Welfare state; Immigrants -- Services for -- Europe; Europe -- Emigration and immigration -- Government policy; Europe -- Emigration and immigration -- Social aspects